Iot Based Smart Jar For Connected Devices Using Machinelearning - R, Neelaveni.; Sridevi, B. (International Journal of Engineering and Technology, 2018)
The smart jar enables us to keep track of the medicines stocks with the help of an android app easily accessible anywhere with a simple internet connection. The jar contains an ultra-sonic sound waves emitter and sensor which uses the reflected ultra-sonic waves to find out what level the jar is filled to and how much empty space remains in jar yet to be filled. This sensor is also connected to the internet and interfaced with the application so that as soon as the level of content in the jar changes the data is updated to us in the application without any delay. This helps us in monitoring the stocks and prepare for restocking from anywhere,additionally it also provides important data such as the expiry date and the manufactured data of the content in the jar.  .
Keywords: smart jar; Internet of things; Pharmacy; medicines Microcontroller.